LEFT VENTRICULAR LEAD PLACEMENT FOR PACING AND SENSING IN A PATIENT WITH ARRHYTHMOGENIC RIGHT VENTRICULAR CARDIOMYOPATHY UNDERGOING ICD IMPLANTATION - Jane Taleski; Manola, Šime; Radeljić, Vjekoslav; Bulj, Nikola; Delić Brkljačić, Diana; Pavlović, Nikola (Sestre Milosrdnice University Hospital Center (KBC Sestre milosrdnice), 2019)
We present a case of a 64-year-old female patient scheduled for implantable cardioverter defibrillator (ICD) implantation due to arrhythmogenic right ventricular cardiomyopathy (ARVC). Dual coil, active fixation ICD lead was introduced through the axillary vein. More than 20 positions were changed in the right ventricle (RV) (outflow tract, high, mid and apical septum, infero-basal, apical and lateral wall). Maximum R wave amplitude was 2 mV with pacing threshold of 0.5 V. Since the sensing was inappropriate, we decided to place the pace/sense lead of the ICD in the coronary sinus. The lead was placed in the basal part of the lateral vein. The pacing threshold was 1.0 V/0.40 ms and R wave was 9 mV. The lead was connected to the ICD sense-pace port and high voltage coils were connected in the usual way. The RV sense-pace lead was capped off. The device sensed an R wave of 7.0 mV 48 hours later. The purpose of this report is to show a possible solution of sensing problems during an ICD implantation in a patient with ARVC.